The Notary's Answer to the Making of the Sale and Purchase Agreement Deed (PPJB) When a Dispute Occurs for the Parties - Fadlulah, Muhammad Ajib (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
The binding sale and purchase agreement which is often called PPJB is made before a notary with the aim of expressing the agreement of the parties in the form of a deed to bind each other. This writing aims to find out and analyze the responsibility of a notary for making a sale and purchase agreement deed when a dispute occurs for the parties in Rembang district and to find out and analyze the juridical implications for making a binding sale and purchase agreement deed when a dispute occurs in Rembang district. The approach method used in this study is a sociological juridical approach, which means a study conducted on the real condition of society or the community environment with the intent and purpose of finding facts which then leads to identification and ultimately leads to problem solving. The analytical knife in this paper uses the theory of legal certainty and the theory of responsibility. The results of this study indicate that the notary's responsibility for the deed he made is limited to the initial part of the deed / head of the deed and the final / closing part of the deed, in this section the notary has full responsibility for its contents both formally and materially. The role of the Notary is only as a Media for the birth of an Authentic Deed and Juridical Implications for Making a Sale and Purchase Binding Agreement Deed in the event of a Dispute in Rembang Regency made before a Notary in which a dispute occurs because one party's obligations are not fulfilled (default) can cause the cancellation of the deed drawn up before a Notary namely the deed of the Sale and Purchase Agreement (PPJB) can be canceled if it does not fulfill the subjective element or is null and void if it does not fulfill the objective element as it turns out in Article 1320 of the Civil Code.Keywords: Agreement; Buy; Sell.